Updated branching fraction measurements of B (s) 0 → K S 0 h + h ′ − decays - LHCb collaboration; Aaij, R; Adeva, B; Adinolfi, M; Evans, T; Gandini, P; Cazon, BR; Hadavizadeh, T; Harnew, N; Hill, D; Jalocha, PG; John, MJJ; et al. (Springer Berlin Heidelberg, 2017)
The charmless three-body decays B (s) 0 → K S 0 h + h ′ − (where h (′) = π, K) are analysed using a sample of pp collision data recorded by the LHCb experiment, corresponding to an integrated luminosity of 3 fb^-1 . The branching fractions are measured relative to that of the B 0 → K S 0 π + π − decay, and are determined to be: (Formula Presented.) at 90% confidencelevel, where f s /f d represents the ratio of hadronisation fractions of the B s 0 and B 0 mesons.